The Influence of Using Animated Videos on the Symbolic Thinking Skills of 5-6 Year Old Children - Sartika, Rindi; Alimudin (UNIB Press, 2025)
This research is motivated by the less-than-optimal symbolic thinking ability of children aged 5-6 years, which is caused by the minimal use of learning media, especially audio-visual media in the form of animated videos. The purpose of this study was to investigate the impact of using animated videos on the symbolic thinking abilities of children aged 5-6 years at Aisyiyah Bustanul Athfal Kindergarten Sumbergede. The method used in this study was quantitative with a quasi-experimental design of the nonequivalent group design type. The research sample consisted of 30 children, with 15 children assigned to the experimental group and 15 to the control group. The results of the hypothesis test using the Independent Sample t-test showed a significance value (2-tailed) of 0.000 < 0.05, indicating a significant effect of using animated videos on the symbolic thinking ability of children aged 5-6 years at Aisyiyah Bustanul Athfal Kindergarten Sumbergede. The findings of this study suggest that the use of animated video media has a positive impact on the symbolic thinking abilities of children aged 5-6 years, compared to conventional methods that rely solely on worksheets.